Azorella compacta's long-term growth rate, longevity, and potential for dating geomorphological and archaeological features in the arid southern Peruvian Andes - Harpel C.J. (2021)
We determine the long-term growth rate and longevity of an Azorella compacta growing on Misti volcano, near Arequipa, Peru to investigate the species' capacity as a geochronological resource. Using 14C dating on stem pieces sequestered within the plant's cushion, which grows larger through time, we obtain ages of 15 ± 15 14C yrs BP and 165 ± 15 14C yrs BP at depths of 15 cm and 29 cm below the cushion's living surface, respectively. Applying a mixed calibration curve with a Bayesian growth model yields calendar age ranges of 1948–1958 CE and 1802–1935 CE for our 14C dates, respectively. Such ages provide sufficiently precise constraints for investigations requiring dating during the last few hundred years when individual 14C dates yield imprecise calendar age ranges. We infer a long-term growth rate of 1.3–3.5 mm yr?1, corroborating published maximum short-term growth rates. Extrapolating our growth model to the A. compacta's core suggests that it began growing as early as 1462–1830 CE. At such age it lived through myriad important geological and historical events, including regional earthquakes, volcanic unrest at Misti, decades to centuries of the Little Ice Age, and a broad transect of Peruvian history possibly beginning during the Inca Empire. A. compacta may provide another important geochronological resource in the arid Central Andes that can be applied to date volcanological, glacial, mass-movement, and archaeological features, especially where dendrochronology and lichenometry are not possible. © 2021